2015
DOI: 10.1080/13607863.2015.1008986
|View full text |Cite
|
Sign up to set email alerts
|

Improving oral health of institutionalized older people with diagnosed dementia

Abstract: Use of ultrasonic baths can be a successful means for improving denture hygiene among older people in long-term care with and without dementia. Education for carer in order to improve oral hygiene, however, seems to be of minor significance and to be more effective for people with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 33 publications
1
36
0
1
Order By: Relevance
“…26 There is currently no consensus on the protocols for assistance by third parties in geriatric centers or at home. [27][28][29] In contrast to other studies, 14 the education variable was not a confounder. Schooling level was associated with both tooth/prosthesis-brushing and the plaque index but not with higher or lower cognitive impairment.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…26 There is currently no consensus on the protocols for assistance by third parties in geriatric centers or at home. [27][28][29] In contrast to other studies, 14 the education variable was not a confounder. Schooling level was associated with both tooth/prosthesis-brushing and the plaque index but not with higher or lower cognitive impairment.…”
Section: Discussionmentioning
confidence: 62%
“…The value of daily tooth‐brushing with electric or manual toothbrushes for plaque control in the elderly is well‐documented and the use of fluorides (mainly in toothpaste) has been described as the most effective and efficient method to prevent caries . There is currently no consensus on the protocols for assistance by third parties in geriatric centers or at home …”
Section: Discussionmentioning
confidence: 99%
“…From our point of view, use of PDC as a first step can provide the basis for implementation of other longterm strategies. 16,[20][21][22][23]35 We have shown that the necessary time frames to provide dental care neither differ between demented and nondemented residents nor between mobile and immobile residents. This finding might provide optimism that oral hygiene procedures can be implemented for all nursing home residents, and the knowledge might reduce restraints when healthcare professionals consider implementing such methods.…”
Section: Discussionmentioning
confidence: 92%
“…According to daily experience, the successful provision of PDC by a dental nurse under the supervision of a cooperating dentist in nursing homes depends on the organization, and often the goodwill, of nursing home personnel and management. From our point of view, use of PDC as a first step can provide the basis for implementation of other long‐term strategies . We have shown that the necessary time frames to provide dental care neither differ between demented and nondemented residents nor between mobile and immobile residents.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation